The current state and development of innovative entrepreneurial structures in the Turkestan region - Mukhamedkhanova, A.B.; Nursoy, M. (BUKETOV BUSINESS REVIEW, 2023)
Object: to study the problems of the development of innovative entrepreneurship in the world and domestic practice in order to develop appropriate proposals for the activation of innovative activity of enterprises in the Kazakh economy on the basis of effective international experience. Methods: in the course of the study, a set of methods of positive, normative, comparative and system analysis, synthesis, generalization and scientific abstraction, as well as mathematical and statistical methods were used. Findings: insufficient development of issues of improving the mechanism for the development of innovative entrepreneurship and the use of international experience accumulated in this area revealed the problems in terms of assessing the risks of transition to the path of innovative development, as well as the formation of competitive advantages for business entities. Entrepreneurial structures when entering the world market. Conclusions: innovative entrepreneurship contributes to increasing the flexibility and adaptation of its structure at the current stage of development of the world economy. In the national economy, innovative enterprises contribute to reducing unemployment during the crisis period, accelerate innovation processes in industries. The intensification of competition under the influence of the post-industrialization of the world economy and the change in the organizational and technological structure of production contribute to the strengthening of the role of innovative small and mediumsized enterprises, since they are able to adapt more quickly and painlessly to these changes.